Sorption of citalopram, irbesartan and fexofenadine in soils: Estimation of sorption coefficients from soil properties - Klement, Aleš; Kodešová, Radka; Bauerová, Martina; Golovko, Oksana; Kočárek, Martin; Fér, Miroslav; Koba, Olga; Nikodem, Antonín; Grabic, Roman (Chemosphere, 2018)
The sorption of 3 pharmaceuticals, which may exist in 4 different forms depending on the solution pH (irbesartan in cationic, neutral and anionic, fexofenadine in cationic, zwitter-ionic and anionic, and citalopram cationic and neutral), in seven different soils was studied. The measured sorption isotherms were described by Freundlich equations, and the sorption coefficients, KF (for the fixed n exponent for each compound), were related to the soil properties to derive relationships for estimating the sorption coefficients from the soil properties (i.e., pedotransfer rules). The largest sorption was obtained for citalopram (average KF value for n = 1 was 1838 cm3 g-1) followed by fexofenadine (KF = 35.1 cm3/n μg1-1/n g-1, n = 1.19) and irbesartan (KF = 3.96 cm3/n μg1-1/n g-1, n = 1.10). The behavior of citalopram (CIT) in soils was different than the behaviors of irbesartan (IRB) and fexofenadine (FEX). Different trends were documented according to the correlation coefficients between the KF values for different compounds (RIRB,FEX = 0.895, p-value<0.01; RIRB,CIT = -0.835, p-value<0.05; RFEX,CIT = -0.759, p-value<0.05) and by the reverse relationships between the KF values and soil properties in the pedotransfer functions. While the KF value for citalopram was positively related to base cation saturation (BCS) or sorption complex saturation (SCS) and negatively correlated to the organic carbon content (Cox), the KF values of irbesartan and fexofenadine were negatively related to BCS, SCS or the clay content and positively related to Cox. The best estimates were obtained by combining BCS and Cox for citalopram (R2 = 93.4), SCS and Cox for irbesartan (R2 = 96.3), and clay content and Cox for fexofenadine (R2 = 82.9).
Keywords: silikáty hliníku; jíl; Citalopram; Pedotransfer rules; Terfenadine; Cationic; Wastewater; Soil Pollutants; zemědělství; Adsorption; irbesartan; látky znečišťující půdu; Tetrazoles; odpadní voda; tetrazoly; citalopram; Anionic; Irbesartan; Soils; Aluminum Silicates; Sorption; bifenylové sloučeniny; Waste Water; Zwitter-ionic and neutral molecules; Pharmaceuticals; Clay; Soil; půda; terfenadin; Biphenyl Compounds; adsorpce; Agriculture